Japan in Analysis - Parker, I. author. aut Link
VI, 179 p.
Keywords: This book is about the development of psychoanalysis and modern subjectivity in Japan, and addresses three key questions: 'Why is there psychoanalysis in Japan?', 'What do we learn about Japan from its own forms of analysis?', and 'What do we learn about ourselves from Japan?'.